'This is not how cancer looks': Celebrity diagnosis and death in the tabloid media. (February 2014) - Ashton, Daniel; Feasey, Rebecca
Jade Goody was publicly diagnosed with cervical cancer in 2008, and prior to her death in 2009 she remained a permanent presence in the celebrity and tabloid press. And although popular commentary refers to the 'Jade Effect' whereby young women, who otherwise would not have gone for testing, are seeking out cervical screening programs after the death of Jade Goody, it is important that we understand the ways in which tabloid readers engage with celebrity news stories. With this in mind this article draws on focus group discussions with young female OK! readers to explore the ways in which they make use of, find comfort in, or take umbrage at the news coverage of celebrity illness, concluding that readers were at best frustrated and at worst angered by a lack of authenticity and candid imagery, which is surprising given the 'airbrushed' and 'orchestrated' nature of their chosen publication.